(untitled) (Oxford, 2006)
Business one: one is the first business english course written specifically for teaching and learning one-to-one.Its non-linear approach allows you to negotiate with your student what the course covers,what happens in each lesson,and how they practise between lessons.
Keywords: English language,English language,Anh ngữ; Business english,Tiếng Anh thương mại